Pengaruh Layanan Bimbingan Kelompok dengan Teknik Diskusi Kelompok terhadap Social Loafing - Wulandari, Adelia; Wibowo, Agus; Pranoto, Hadi (Counseling Milenial (CM), 2025)
This study intends to ascertain how group guidance services and group discussion technique at SMP Negeri 1 Kotagajah affect social loafing. This study used a single group pre-test/post-test experimental quantitative research methodology. The sample for this study consisted of 7 eighth-grade students from SMP Negeri 1 Kotagajah. A social loafing questionnaire is used as the data gathering method. The findings of the study have an impact on students both before and after the introduction of group assistance services using discussion approaches. Average pre-test scores were 68.86, while post-test scores were 103.57. The average post-test score is greater than the pre-test score on average, demonstrating the impact of group guidance services and group discussion approaches on students' social loafing. The t test calculation findings, which indicate tcount> ttable (6.078> 1.94318) with a significant level of 0.05, support this. Based on the findings of the t test analysis, it is possible to draw the conclusion that H0 is rejected and H1 is accepted. This suggests that group guidance services combined with group discussion approaches have an impact on social loafing at SMP Negeri 1 Kotagajah in the academic year 2022/2023.